Body composition and cross-sectional areas of limb lean tissues in Olympic weight lifters - Kanehisa, H.; Ikegawa, S.; Fukunaga, T. (Scandinavian Journal of Medicine & Science in Sports, 1998)
The cross-sectional area (CSAs) of bone and muscle tissues in the forearm, upper arm, lower leg, and thigh and body composition were determined by B-mode ultrasound and underwater weighing methods, respectively for 56 college Olympic weight lifters and 28 age-matched non-athletes to investigate the magnitude of musculoskeletal development in the strength-trained athletes belonging to the weight-classified sports event. The average value of fat-free mass (FFM) for the weight lifters ranked 12.6 kg above the regression line of FFM on stature for untrained subjects. In the weight lifters, however, the percentage of fat mass to body mass was also highly correlated to body mass index. Bone and muscle CSAs in every site were significantly larger in the weight lifter than in the untrained subjects with relative differences of 22 to 58% and 17 to 56%, respectively. Moreover, as a result of regression analysis for the mixed data from weight lifters and untrained subjects, significant correlation was found between bone and muscle CSAs in every site (r = 0.620 to 0.791, P < 0.05). The differences in lean (bone + muscle) CSA were still significant in all sites except for the lower leg even when the difference in body size was statistically controlled. The comparisons between the weight lifters and untrained subjects on the lean CSA ratios of site to site and muscle CSA ratios of flexors to extensors indicated that the weight lifters had achieved a high relative distribution of lean tissues in the arms and a dominant development in elbow and knee extensors. Thus, the present results suggested that participation in weight lifting exercises for a long period could increase bone CSA as well as muscle CSA, and induce in the participants a noticeable enlargement in given sites and muscle groups responsible for performing the Olympic lifts.